Penegakan Hukum terhadap Pelaku Tindak Pidana Kekerasan Seksual (Studi di Polresta Sidoarjo) - Nabilla Tasya Shalsahbila; Yana Indawati (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2023)
This study will concentrate on the legal actions taken by the Sidoarjo Police against those who commit offenses involving sexual violence in the Sidoarjo Regency. To provide legal clarity for the society, law enforcement actions are taken against those who commit offenses including sexual violence. The goal of this study was to examine how the Sidoarjo Police enforced the law against those who committed crimes involving sexual assault in the Sidoarjo Regency, as well as to identify any challenges that had to be overcome in this regard. This study employs a qualitative data analysis approach and is legal-empirical in nature. Interviews, data gathering techniques, and literature analysis were all used in this study. Based on the study's findings, it can be seen that the Sidoarjo Polresta carries out a process of preliminary and thorough inquiry against those who commit crimes involving sexual violence so that they can later be prosecuted in accordance with the provisions of the relevant law., The obstacle is limited authority as a result of unratified implementing regulations, uncooperative suspects as the investigation moves forward, and society's general lack of legal awareness are all obstacles that arise in the law enforcement effort.